Wassenberg, Birte; Reitel, Bernard; Peyrony, Jean and Rubió, Jean (2015). Territorial Cooperation in Europe - A Historical Perspective - Rubió, Jean (Documents d’Anàlisi Geogràfica, 2018)
Wassenberg, Birte; Reitel, Bernard; Peyrony, Jean and Rubió, Jean (2015) Territorial Cooperation in Europe - A Historical Perspective Luxemburg: Publications Office of the European Union, 172 p. ISBN 978-92-79-49499-4